Assessment of effects of idealized defect shape and width on the burst capacity of corroded pipelines. (September 2020) - Zhang, S.; Zhou, W.
Abstract: This study investigates the burst capacities of corroded pipelines using three-dimensional elasto-plastic finite element analyses validated by full-scale burst tests of corroded pipe specimens reported in the literature. The semi-ellipsoidal idealization of naturally-occurring corrosion defects in FEA is found to lead to more accurate predictions of the burst capacity than the rectangular idealization for defects that are less than 70% through the pipe wall thickness. Results of extensive parametric FEA based on the semi-ellipsoidal idealization of the corrosion defects indicate that the burst capacity in general increases as the defect width increases if the defect depth and length remain the same. The defect width effect is marked for deep, relatively short defects, and should therefore be taken into account accordingly in the empirical or semi-empirical burst capacity models. The defect width effect is marginal for long defects with w/l ≤ 1.5. The observed width effects are explained by considering the change in the membrane and bending stresses in the defect region as the defect width increases. Highlights: Investigate the burst capacity of corroded pipelines using extensive 3D elasto-plastic FEA. Compare the rectangular and semi-ellipsoidal idealizations of corrosion defects. Investigate the effect of the defect width on the burst capacity based on semi-ellipsoidal idealization. Defect width is found to have a beneficial effect on the burst capacity of corroded pipelines.